How to translate 'good governance' into Tajik? An American good governance fund and norm localisation in Tajikistan - Kluczewska, Karolina (Journal of intervention and statebuilding)
This article analyses how international norms are transferred to aid-receiving countries and with what outcomes, when tensions exist between these norms and local realities. By taking a case study of an American-funded good governance project in Tajikistan, it investigates a multi-level and multi-actor process of norm localisation, looking at why and how different development agencies re-appropriate international norms. The article proposes to see a failed localisation from the point of view of donors, in a way that outcomes differ from their initial intentions, as a successful localisation from the point of view of local actors. The distortion of international norms indicates that local actors re-appropriated them in accordance with their biographies, personal views, and political opportunities and constraints of organisations which they represent.